1. PF Contest - Win "Conquering the Physics GRE" book! Click Here to Enter
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Show that [A, F(B)] = [A, B]F'(B)

  1. Feb 29, 2016 #1
    1. The problem statement, all variables and given/known data
    A and B commute with their commutator, C=[A,B]
    Show that [A, F(B)] = [A, B]F'(B)
    F(B) = ∑n=0fnBn

    2. Relevant equations
    [A,B] = AB - BA
    [A,BC] = [A,B]C + B[A,C]

    3. The attempt at a solution
    So all I can think to do is:
    [A,Bn] = [A,BBn-1] = [A,B]Bn-1 + B[A,Bn-1]
    =ABBn-1 - BBn-1A
    and this seems to be a dead end? Just loops back around to ABn - BnA
    If this is along the right track, whereabouts would I go next? If this is not the way to start it, how would I go about beginning this problem?
    And even if this is along the right lines, I've ignored the sum here as I'm not quite sure how that affects the whole thing.

    Thanks for your time
  2. jcsd
  3. Feb 29, 2016 #2


    User Avatar
    Science Advisor
    Homework Helper

    Start by showing the case where f(B)=B^2. You should get [A,f(B)]=[A,B]2B. Which is [A,B]f'(B). Then try f(B)=B^3. For the general case use induction to prove if f(B)=B^n, then [A,B^n]=[A,B]nB^(n-1). Which is [A,B]f'(B). Now deal with the sum.
  4. Mar 1, 2016 #3
    Ooh ok thanks.
    So I went through it with n=2,3 and 4 and [A, F(B)] = [A, B]F'(B) was shown for each of them.
    For the sum is it simply that when n is any value, fn is a constant so that
    (for example)
    [A,f2B2] = [A, f2B]B + f2B[A, B]
    f2 a constant and can be taken outside of [] as it effect both sides the same so (and as B commutes with [A, B])
    [A, f2B]B + f2B[A, B] = [A,B]f2B + [A,B]f2B
    =[A,B]2f2B = [A, B]F'(B)
    Is this how it's shown?
  5. Mar 1, 2016 #4


    User Avatar
    Science Advisor
    Homework Helper

    Yes, the Lie bracket is linear over scalars, so ##[A,cf(B)+dg(B)]=c[A,f(B)]+d[A,g(B)]##. That's how you take care of the sum. It's good that you've shown it works for n=2,3 and 4. To show it's true for general ##n## that ##[A,B^n]=[A,B]nB^{n-1}## there's a general procedure called mathematical induction. You assume it's true for ##n## and then show that it must be true for ##n+1##. Since you've already shown that it works for small values of n, that shows it works for all values of n. A less formal argument is to show, for example, that ##[A,B^3]=[A,BBB]=[A,B]BB+B[A,B]B+BB[A,B]## and then say this pattern holds for all n.
    Last edited: Mar 1, 2016
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted